2023
DOI: 10.3389/fmed.2023.1023383
|View full text |Cite
|
Sign up to set email alerts
|

Indoxyl sulfate mediates low handgrip strength and is predictive of high hospitalization rates in patients with end-stage renal disease

Abstract: Background and aimsSarcopenia has a higher occurrence rate in patients with chronic kidney disease (CKD) and end-stage renal disease (ESRD) than in the general population. Low handgrip strength—and not sarcopenia per se—is associated with clinical outcomes in patients with CKD, including cardiovascular mortality and hospitalization. The factors contributing to low handgrip strength are still unknown. Accordingly, this study aimed to determine whether uremic toxins influence low handgrip strength in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…The in vivo study demonstrated the similar number of nuclei in the skeletal muscle, and the myoD expression was similar after IS treatment in the in vitro study. The clinical data demonstrated that the skeletal muscle mass did not have the association with the concentration of indoxyl sulfate [ 24 ]. Therefore, the IS might not influence the skeletal muscle viability or the direct destruction on the myotube.…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo study demonstrated the similar number of nuclei in the skeletal muscle, and the myoD expression was similar after IS treatment in the in vitro study. The clinical data demonstrated that the skeletal muscle mass did not have the association with the concentration of indoxyl sulfate [ 24 ]. Therefore, the IS might not influence the skeletal muscle viability or the direct destruction on the myotube.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent clinical cohort found that ESRD patients had low handgrip strength, possibly due to higher levels of IS [143]. Elevated IS levels are associated with muscle issues, and incorporating AST-120 in CKD treatment shows promise for improving sarcopenia [144].…”
Section: Crosslinks Between Bones and Musclesmentioning
confidence: 98%
“…Indoxyl sulfate, which is derived from the breakdown of tryptophan, is the most studied uremic toxin in regard to pathologic actions on tissues. The elevated serum levels of indoxyl sulfate are associated with reduced muscle strength in ESRD patients [217]. Experimental studies have shown that indoxyl sulfate induces morphological changes in mitochondria, impairs mitochondrial function, and stimulates excessive ROS production and myostatin expression, resulting in myofiber atrophy [85,[218][219][220].…”
Section: Mechanisms Of Ckd-associated Sarcopeniamentioning
confidence: 99%